Mitochondrial disruption in Drosophila apoptosis. - Abdelwahid, E.; Yokokura, T.; Krieser, R.J.; Balasundaram, S.; Fowle, W.H.; White, K. (Developmental Cell, 2007)
Mitochondrial disruption is a conserved aspect of apoptosis, seen in many species from mammals to nematodes. Despite significant conservation of other elements of the apoptotic pathway in Drosophila, a broad role for mitochondrial changes in apoptosis in flies remains unconfirmed. Here, we show that Drosophila mitochondria become permeable in response to the expression of Reaper and Hid, endogenous regulators of developmental apoptosis. Caspase activation in the absence of Reaper and Hid is not sufficient to permeabilize mitochondria, but caspases play a role in Reaper- and Hid-induced mitochondrial changes. Reaper and Hid rapidly localize to mitochondria, resulting in changes in mitochondrial ultrastructure. The dynamin-related protein, Drp1, is important for Reaper- and DNA-damage-induced mitochondrial disruption. Significantly, we show that inhibition of Reaper or Hid mitochondrial localization or inhibition of Drp1 significantly inhibits apoptosis, indicating a role for mitochondrial disruption in fly apoptosis.